Recent developments in the determination of the amplitude and phase of quantum oscillations for the linear chain of coupled orbits - Audouard, А.; Fortin, J.-Y. (Физика низких температур, 2014)
De Haas-van Alphen oscillations are studied for Fermi surfaces (FS) illustrating the model proposed by
Pippard in the early sixties, namely the linear chain of orbits coupled by magnetic breakdown. This FS topology
is relevant to many multiband quasi-two-dimensional (q-2D) organic metals such as -(BEDT–TTF)₂Cu(NCS)₂
and -(BEDT–TTF)₄CoBr₄ (C₆H₄Cl₂) which are considered in detail. Whereas the Lifshits–Kosevich model only
involves a first order development of field- and temperature-dependent damping factors, second order terms
may have significant contribution to the Fourier components amplitude for such q-2D systems at high magnetic
field and low temperature. The strength of these second order terms depends on the relative value of the involved
damping factors, which are in turns strongly dependent on parameters such as the magnetic breakdown field, effective
masses and, most of all, effective Landé factors. In addition, the influence of field-dependent Onsager
phase factors on the oscillation spectra is considered.